2012
DOI: 10.1016/j.electacta.2012.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and vanadium oxynitride powders as pseudo-capacitive materials for electrochemical capacitors

Abstract: International audienceTiOxNy and VOxNy powders have been synthesized using oxide precursors and a conventional nitridation method. It enables to control of oxygen content and surface area. The electrochemical performances of the different powders have been investigated. A strong dependence on the surface area as well as on the nature of the oxynitride has been found. A typical value of 300 μF cm−2 has been determined for VOxNy powders, while TiOxNy powders only show 50 μF cm−2. In this last case it is believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…7a at the current density of 1 A g À1 suggests poor cycling stability of VN. The similar phenomenon can be observed in other reports [35,[44][45][46][47]. For example, Choi et al found the capacitance of nanocrystalline VN remains about 1% after 1000 cycles [35], and Lu et al report the capacitance of pristine VN nanowire decreases rapidly, and only 8.5% of initial capacitance remained after cycling [44].…”
Section: Resultssupporting
confidence: 71%
“…7a at the current density of 1 A g À1 suggests poor cycling stability of VN. The similar phenomenon can be observed in other reports [35,[44][45][46][47]. For example, Choi et al found the capacitance of nanocrystalline VN remains about 1% after 1000 cycles [35], and Lu et al report the capacitance of pristine VN nanowire decreases rapidly, and only 8.5% of initial capacitance remained after cycling [44].…”
Section: Resultssupporting
confidence: 71%
“…As a proof of concept, we prepared self-supported carbon coated TiN (notated as C-TiN) nanotube arrays because recently metal nitrides have received much attention in the eld of electrochemical energy storage. 17 We believe that this technique could further be benecial to many other material systems and applications because of the versatility of this approach. Importantly, we could demonstrate that the long-term cycling ability of C-TiN compared to bare TiN nanotube arrays is strongly improved due to the functional carbon coating, which is, to the best of our knowledge, a key challenge for metal nitride materials in electrochemical energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they also showed that when coating VN with carbon, the electrode kept up to 88% of its initial capacitance after 15000 cycles in 1 M KOH. All these studies highlight the need of in-depth investigations of the suitable conditions for which VN is stable as an active material for energy storage applications.Most studies use VN powders prepared via ammonolysis of various vanadium oxides 40,42,44,45,48,49,53,60 or chloride. 37,58 As pointed out by Porto et al,46 this gives rise to two main drawbacks: (1) the use of different precursors especially oxides may lead to difference in compositions and especially oxygen content in the VN powders and (2) the use of powders imply the use of carbon and polymer additives in order to prepare composite electrodes, thus preventing the study of VN intrinsic electrochemical properties.…”
mentioning
confidence: 99%
“…Accordingly, several research groups considered materials such as MXenes 29,30 and transition metal nitrides. [31][32][33][34][35][36][37] In the latter class of compounds, molybdenum nitride was firstly investigated 32,33,35,38,39 and in the past decade a great deal of attention has focused on other nitrides with an intensive focus on vanadium nitride 37,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] as a consequence of the impressive capacitance of 1340 F.g −1 reported for nanosized VN particles in 1 M KOH. 58 Indeed, VN is an interesting electrode material due to this high reported specific capacitance coupled with its close to metallic electronic conductivity (1.18 S.m −1 ), 59 high density (6.13 g.cm −3 ) and high melting point (2619 K).…”
mentioning
confidence: 99%